posted by .

(12x + 5t)-(14t-6x)
12x + 5t - 14t -6x ( I get lost here when the -6x changes to +6.

Same as this question:
(5x + 2z)-(2x - 11z)

Can anyone explain this to me? Thank you

  • Algebra -

    (12x + 5t)-(14t-6x)
    12x + 6x - 14t + 5t
    18x - 9t

    Try the next one and we'll check it for you.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. algebra2

    1/3 - 5/6 = 1/X SOLVE 1/3 - 5/6 = 1/X Let's remove the denominators by multiplying by 12X 12X*(1/3) - 12X*(5/6) = 12X*(1/X) Clear the fractions. 4X - 10X = 12 -6X=12 multipy by -1 6X=-12 Divide both sides by 6 6X/6 = -12/6 X = -2 Check …
  2. Calculus

    Consider the parametric curve given by the equations x(t)=t^2–14t–4 y(t)=t^2–14t+48 How many units of distance are covered by the point P(t) = (x(t),y(t)) between t=0, and t=11 ?
  3. algebra

    5x -3 = 11 + 12x combine like figures add 3 to both sides to remove the 3 5x= 14+ 12x Now I get confused. If I remove the 12x I have to subtract 12x from 5x which gives me an answer of -7x=14 would the correct answer thus be x= -2?
  4. algebra

    24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please
  5. Math

    The population size, P, of owls (predators) in a certain region can be modelled by the function P(t) = 1000 + 100 sin (3.14t/12), where t represents the time in months. The population size, p, of mice (prey) in the same region is given …
  6. please help math

    Simplify the expression. 7t^4*7t^4 A.49t^8 B.14t^4 C.49t^16 D.14t^4 Is the answer A?
  7. Algebra. Please check my answers

    Evaluate a/b+c^d for a=6,b=3,c=4 and d=5 A.42*** B.18 C.82 D.360 What is the simplified form of the expression ?
  8. math

    7t^4x7t^4 a. 49t^8** b. 14t^4 c. 49t^16 d. 14t^8
  9. Physics

    Hello, I need that someone help me with this excersise. I have to calculate (USING INTEGRATION) the motion ecuation of a particle. The excersise give me the ecuation of the velocity that is v=14t-32 , the initial time t1=3 And the …
  10. Algebra

    What is the vertex form of the equation? y = -x^2+12x-4 My work: -(x^2 + 12x)-4 -(x^2 + 12x + 36)-4 + 36 Y= -(x+36)^2 + 32 Is this correct?

More Similar Questions